DISHphagia and DISHphonia DISHguised as a stroke - Abdulrahman Khalid Alfadhel; Abdullah K Almanea; Rajkumar Rajendram; Abdulaziz G Alsaad (Wolters Kluwer Medknow Publications, 2020)
Diffuse idiopathic skeletal hyperostosis (DISH) is a noninflammatory condition that usually affects the elderly patients with several metabolic derangements. It is characterized by symptoms that mimic more sinister conditions such as stroke or malignancy. Indeed, this diagnosis can easily be "DISHmissed" if not considered in the differential diagnosis. Dysphagia is the most common symptom reported by patients with DISH. Always due to cervical osteophytes, dysphagia due to DISH has been described as DISHphagia. Extrapolation of this terminology to DISHphonia, DISHpnea, DISHpepsia, and DISHesthesia may increase awareness of the plethora of symptoms that may be caused by DISHplacement of anatomy. This is clinically significant because the prevalence of DISH is likely to increase, and DISH can be managed with conservative, medical, and surgical therapies.